Pengaruh Metode Pembelajaran Artikulasi Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi di SMA Setia Darma Palembang - Putri, Kania Intan; Aradea, Riswan; Toyib, M. (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The purpose of this study is to find out the effect of the application of articulated learning methods on student learning outcomes in Economics subjects at SMA Setia Darma Palembang for the 2024/2025 Academic Year. The research method used is an experimental method with a quantitative approach. The results of the study showed that there was an effect of the application of the articulation learning method on student learning outcomes in Economics subjects at SMA Setia Darma Palembang for the 2024/2025 school year. This result is evidenced by a significant level of tt 5% < t0 > tt 1% or 2.03 < 6.48 > 2.79. Thus Ha was accepted and Ho was rejected. And the average score of the pre-test results of class XI 2 was 5.86. Meanwhile, the average score of the post test results of class XI 2 has increased by 7.61.